Prevalence of Antibiotic Profile Among Patient In Selective Major Hospitals Sana'a, Yemen 2023 - Aljanadi, Ala'a Hasan; Alqbaty, Doa'a Fouad; Zayed, Fatima Abdu; Alsaby, Halah Waheed; Almogany, Hassena Hafedallah (My University, 2023)
Background: Antibiotic is a type of medication used to combat bacterial infections in the body. The development of antibiotic resistant is a major problem in clinical practice. Many patients suffer from antibiotic resistant infections, which reduces the effectiveness of treatment and increases the difficulty of getting rid of the infection. Antibiotic sensitivity refers to the ability of bacteria or other microorganisms to respond to the effects of antibiotics. Aim: To determine prevalence of antibiotic profile in selective major hospital Sana'a city 2023.